Systematic Review: Factors Affecting Community Participation in JKN-KIS - Vini Restu Insani; Jon Hendri Nurdan; Fiya Diniarti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The National Health Insurance (JKN) is a program that aims to provide comprehensive health insurance for every Indonesian so that the Indonesian people can live healthy, productive, and prosperous lives. Health behavior is basically a person's response to stimulation related to illness and disease in the health care system, food, and the environment. However, there are several factors that cause people to still not follow JKN-KIS. One of them is the behavioral factor according to Lawrence Green, where the factors that influence health behavior to consist of 3 factors, namely the first predisposing factor (Presdiposing Factor) which consists of the knowledge and attitudes of a person or society toward what will be done, the second is a supporting factor ( Enabling Factor) namely facilities,  facilities, or infrastructure that support or facilitate the occurrence of a person's or community's behavior and the third is a motivating factor (Reinforcing Factor), namely encouragement, advice and motivation that comes from parents, husband/wife, children, family, leaders community and health workers given to participants to become JKN-KIS participants. If the three factors of health behavior are found to be unfavorable, it will certainly affect community satisfaction and will affect the low number of people participating in JKN-KIS. This study was conducted to determine the behavioral factors that have the most role in influencing the community to participate in JKN-KIS. Systematic reviews were carried out on 50 journals uploaded to Google Scholar and Pub Med from 2015 to 2021. The most dominant factor influencing people to follow JKN-KIS is the reinforcing factor, namely encouragement, advice, and motivation that comes from social support, namely parents, husband/wife, children, family, community leaders and health workers provided respondents to become JKN-KIS participants.